Social media in shaping public opinion roles and impact: a systematic review - Dasad Latif; Muhammad Ahsan Samad; Rinawulandari; Shamsiah Abd Kadir (Penerbit Universiti Kebangsaan Malaysia, 2024)
This systematic literature review examines the impact of social media on public opinion and its implications for policy-making. Utilising the PRISMA framework, the study analysed 19 articles from Scopus and Web of Science databases published between 2013-2023. The review identified five main categories of social media platforms discussed; Twitter/X, Meta (Facebook, Instagram, WhatsApp), YouTube, Chinese apps (Sina Weibo, WeChat, QQ), and several unspecified platforms. Key themes emerged across these categories, including the role of social media in knowledge dissemination, creation of filter bubbles and echo chambers, amplification of diverse voices, and spread of misinformation. The findings highlighted social media potential for real-time public opinion monitoring, facilitating engagement between policymakers and citizens, and early identification of emerging issues. However, challenges such as information credibility and algorithmic curation of content were also noted. The review suggests that strategic use of social media can raise awareness and mobilise support for global initiatives like the Sustainable Development Goals. It emphasises the need for policymakers to understand and leverage social media's influence on public sentiment while addressing associated risks. The study contributes to a nuanced understanding of how different social media platforms shape public discourse and influence policy decisions in the digital age. Future research directions are proposed to further explore the complex dynamics between social media, public opinion, and governance in an evolving technological landscape.